Investigation of α,ω-Disubstituted Polyamine-Cholic Acid Conjugates Identifies Hyodeoxycholic and Chenodeoxycholic Scaffolds as Non-Toxic, Potent Antimicrobials - Kenneth Sue; Melissa M. Cadelis; Thomas Troia; Florent Rouvier; Marie-Lise Bo; Jean Michel Brunel; Brent R. Copp (MDPI AG, 2023)
With the increased incidence of antibiotic resistance, the discovery and development of new antibacterials is of increasing importance and urgency. The report of the natural product antibiotic squalamine in 1993 has stimulated a lot of interest in the study of structurally simplified cholic acid-polyamine derivatives. We report the synthesis of a focused set of deoxycholic acid-polyamine conjugates and the identification of hyodeoxycholic acid derivatives as being potently active towards S. aureus MRSA and some fungal strains, but with no attendant cytotoxicity or hemolytic properties. Analogue 7e exhibited bactericidal activity towards a range of Gram-positive bacteria, while preliminary investigation of its mechanism of action ruled out the bacterial membrane as being a primary cellular target as determined using an ATP-release bioluminescence assay.